Associations Between Levels of High-Sensitivity C-Reactive Protein and Outcome After Intracerebral Hemorrhage - Wang, Jing; Wang, Wenjuan; Liu, Yanfang; Zhao, Xingquan (Frontiers in Neurology, 2020)
Background: Patients with spontaneous intracerebral hemorrhage (ICH) have high rates of mortality and morbidity rates; approximately one third of patients with ICH experience hematoma expansion (HE). The spot sign is an established and validated imaging marker for HE. High-sensitivity C-reactive protein (hs-CRP) is an established laboratory marker for inflammation and secondary brain injury following ICH. Objective: To determine the association between the spot sign and hs-CRP, hematoma expansion, and clinical outcomes. Methods: In this multi-center, prospective, cohort study, we recruited 92 patients with spontaneous ICH within 24 h of the onset of symptoms. ICH was diagnosed in the emergency room by non-contrast computed tomography (NCCT) scans. Follow-up scans were carried out within 48 h to evaluate patients for HE. Multidetector computed tomography angiography (MDCTA) was also used to identify spot signs. Blood samples were collected from each patient at admission in EDTA tubes (for plasma) or vacutainer tubes (for serum). hs-CRP values were determined by a particle-enhanced immunoturbidimetric assay in the laboratory at Beijing Tiantan Hospital, Capital Medical University. Patients were categorized into two groups according to their hs-CRP levels (hs-CRP ＜3 mg/l; hs-CRP ≥ 3 mg/l). Results: The incidences of spot sign and HE in our study cohort were 31.5% and 29.3%, respectively. Following the removal of potential confounding variables, stepwise-forward logistic regression analysis identified that an hs-CRP level ≥ 3 mg/l was not a significant indicator for either spot sign (p=0.68) or HE (p=0.07). However, an hs-CRP level ≥ 3 mg/l (odds ratio: 16.64; 95% confidence interval: 2.11–131.45, p=0.008) was identified as an independent predictor of an unfavorable outcome one year after acute ICH. Conclusions: Our analyses identified that an hs-CRP level ≥ 3 mg/l was a significant indicator for an unfavorable outcome one year after acute ICH.